HAY YIELD OF DESERT FORAGE PLANT SPECIES USED THROUGHOUT THE YEAR - A.S.Bobayeva (Web of Journals Publishing, 2025)
The article provides a description of the productivity of promising types of pasture forage plants for use in increasing the productivity of degraded natural pastures.
Keywords: desert, adyr, pastures, degradation, forage, hay, survival, productivity, phytomelioration.